THE ROLE OF CIVIL SOCIETY IN ADVANCEMENT OF DEMOCRACY IN SOUTH AFRICA - Phoke Alpha Ragwata (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
In South Africa, a nation dealing with issues like socioeconomic inequality and governmental corruption, this study explored the vital role that civil society plays in promoting democracy. The aim was to examine the ways in which civil society organizations support civic engagement, hold the government responsible, and aid in democratic processes. The study highlights the diverse contributions of civil society by synthesizing existing literature, reports, and case studies using a thorough desktop research process. Results shows that civil society serves as a watchdog, promoting openness and human rights while also increasing public awareness and involvement. In order to preserve and improve democratic norms and guarantee a fairer and more inclusive political environment in South Africa, the conclusion highlights the importance of bolstering civil society.